POTENTIAL SOURCES OF SUBCRUSTAL MAGMAS - Bogatikov O.A.; Lazko Ye.Ye.; Sharkov Ye.V. (My University, 1990)
On the basis of available data, we have tried to identify known plutonic rocks with the material of hypothetical mantle reservoirs of basaltic and ultramafic magmas. For this purpose, we had to introduce the concept of mantle-substrate types, which can be defined as chemically individualized subcrustal rock assemblages. The latter, because of their composition, either could be the direct sources of various melts, which then crystallize as specific igneous rocks, or make a definite contribution to the properties of such melts. Thus, subcrustal rocks can be classified according to their chemical properties and potential capacity for providing magma of one type or another. However, the relationships between mantle substrates and the possible melts sweated out from them will be analyzed in detail in the next stage of our work. Here we should note merely that the above examples of discrepancies in chemical composition, trace-element content and isotopic characteristics of deep-seated material do not just illustrate its complex evolution. They also indicate that there still are many unsolved problems in the way of creating a standard scheme of genetic relationships between volcanics and their parent rocks.